Discussion - Of Mr. Cook's Paper on Experience with the Gayley Dry Blast at the Warwick Furnaces, Pottstown, Pa. (see p. 705) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
EdgaR S. Cook, Pottstown, Pa.:—Many friends and acquaintances seem to be under the impression that the Warwick Iron & Steel Co. received a' license from Mr. Gayley, free of cost, as an inducement to adopt the process. This impression is not correct, since the license was paid for, and I think it was the first payment that Mr. Gayley received for the use of his process. As president of the Warwick Iron & Steel Co., I am responsible for its earnings, and with only the experience at the Isabella furnaces as a guide, the directors of the company considered that there was a great risk in expending the large sum of money required for the plant. They, however, acted favorably upon my recommendation, and to this extent I am responsible for the installation at the Warwick furnaces. I made the best agreement possible with Mr. Gayley, and naturally our company received certain advantages. It will be contrary to all experience if subsequent plants do not show some improvements and economies in construction. It is to our indirect benefit that all subsequent licenses granted by Mr. Gayley should be charged at a much higher rate than we paid; and I trust that he will see to it that all such licenses granted, especially to companies making merchant iron, shall be at a maximum figure. The Warwick Iron & Steel Go. is not interested in any way in exploiting the merits of the Gayley dry-blast process; on the contrary, looking at the subject from a narrow and selfish standpoint, it is to the advantage of our company that no merchant blast-furnace competing with our iron-product should be equipped with a dry-blast plant. There is a clause in the contract with Mr. Gayley, whereby our company agrees to furnish him with all the data derived from the operation of the dry-blast plant, and that he or his